Analysis of binding affinity of sugars to concanavalin A by surface plasmon resonance sensor BIACORE. Issue 3 (2002) - Goto Goto, Satoru Satoru; Terada Terada, Hiroshi Hiroshi
Abstract : The observed dissociation constant k d of the lectin concanavalin A (ConA) from glycoprotein asialofetuin (ASF) changed with the concentration of inhibitory sugars. The reciprocal of k d showed a linear relationship with the reciprocal of sugar concentration. This regression line was found to be theoretically available in the analysis of the kinetics in the interaction of sugars with ConA under conditions where the binding constant K i of sugars to ConA is more than about 333.